2022
DOI: 10.1002/ejic.202200334
|View full text |Cite
|
Sign up to set email alerts
|

Seven Europium(III) Complexes in Solution – The Importance of Reporting Data When Investigating Luminescence Spectra and Electronic Structure

Abstract: Despite significant effort, the complexity of europium(III) luminescence in general -and sample composition in particular -has precluded the publication of standard spectra of specific complexes in aqueous solution. Further, low spectral resolution, weighted averages with contributions from several species, as well as poor reproduction hampers the use of literature data, with the note that high quality data from e. g. Bünzli, Latva, Carnall, Parker, Heller, Balzani and Sabatini is from the preelectronic era. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
(44 reference statements)
2
13
0
Order By: Relevance
“…From this it can be seen that Eu·DOTA displays different emitting species while Eu·DPA and Eu·EDTA do not. In previous work, speciation studies of these three complexes were carried out by recording the lifetimes of europium­(III) at different concentration equivalents of the three ligands. , Here it is found that Eu·DOTA indeed has multiple lifetimes that can be assigned to the different forms of different symmetry, c-SAP and TSAP, that these complexes are known to possess in solution. , Eu·EDTA primarily displays a speciation between the aqua ion and the EDTA complex. At 1.2 equiv of EDTA, as used in this work, mostly the EDTA complex was observed, although the aqua ion cannot be completely dismissed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…From this it can be seen that Eu·DOTA displays different emitting species while Eu·DPA and Eu·EDTA do not. In previous work, speciation studies of these three complexes were carried out by recording the lifetimes of europium­(III) at different concentration equivalents of the three ligands. , Here it is found that Eu·DOTA indeed has multiple lifetimes that can be assigned to the different forms of different symmetry, c-SAP and TSAP, that these complexes are known to possess in solution. , Eu·EDTA primarily displays a speciation between the aqua ion and the EDTA complex. At 1.2 equiv of EDTA, as used in this work, mostly the EDTA complex was observed, although the aqua ion cannot be completely dismissed.…”
Section: Resultsmentioning
confidence: 90%
“…In previous work, speciation studies of these three complexes were carried out by recording the lifetimes of europium(III) at different concentration equivalents of the three ligands. 42,62 Here it is found that Eu•DOTA indeed has multiple lifetimes that can be assigned to the different forms of different symmetry, c-SAP and TSAP, that these complexes are known to possess in solution. 43,63 Eu•EDTA primarily displays a speciation between the aqua ion and the EDTA complex.…”
Section: Population Analyses Of Optical Transitions Of Europium(iii)mentioning
confidence: 91%
“…3 In all spectra, the 5 D 0 → 7 F 0 is present as expected for [Eu(DOTA)(H 2 O)] − complexes because the crystal field does not have mirror symmetry when nitrogen and oxygen donor atoms are coordinating to the metal ion. 36 A high symmetry fourfold rotation axis persists along the capping water molecule, which can be seen in the 5 D 0 → 7 F 1 transition, which is split in three when the symmetry is lowered. 37 The emission spectra in Fig.…”
Section: Luminescence Spectroscopymentioning
confidence: 98%
“…Little is known of lanthanide(III) solution structure, and the constitution has been debated. 32,35,177 At present this leaves two routes to be investigated: kinetically inert complexes, 178 and simple solvates. For the former the constitution is unchanged when they are dissolved, for the latter the sample composition can be controlled in a manner that ensures that the constitution is known.…”
Section: Telecommunication and Morementioning
confidence: 99%